DIRECT-TO-CONSUMER ADVERTISING OF PRESCRIPTION MEDICINES : SEBUAH KONSEP KONTRIVERSI DALAM MEMBANGUN MEREK INDUSTRI FARMASI (Fokus Ekonomi, 2009)
Implemention of selling and producting concepts have been key success of funtastic growth of pharmaceutical industry for the last decade which supported by R&D program and selling forces. However, increasing customer value expectation toward healthcare products quality and market saturated become challenges for pharmaceutical industry to create brand identity and brand image for building long-term brand equity toward promotion, communication and education process. One of the rising and controversial models for pharmaceutical product’s promotion is Direct-to-Consumer Advertising (DTCA). This article offer the description of DTCA model and its trade-off from customer, medical community and pharmaceutical industry perspectives.